Platelet-neutrophil complex formation—a detailed in vitro analysis of murine and human blood samples. Issue 5 (17th November 2015) - Mauler, Maximilian; Seyfert, Julia; Haenel, David; Seeba, Hannah; Guenther, Janine; Stallmann, Daniela; Schoenichen, Claudia; Hilgendorf, Ingo; Bode, Christoph; Ahrens, Ingo; Duerschmied, Daniel
Abstract : Technique to measure murine and human PNC formation in whole blood samples. Abstract: Platelets form complexes with neutrophils during inflammatory processes. These aggregates migrate into affected tissues and also circulate within the organism. Several studies have evaluated platelet-neutrophil complexes as a marker of cardiovascular diseases in human and mouse. Although multiple publications have reported platelet-neutrophil complex counts, we noticed that different methods were used to analyze platelet-neutrophil complex formation, resulting in significant differences, even in baseline values. We established a protocol for platelet-neutrophil complex measurement with flow cytometry in murine and human whole blood samples. In vitro platelet-neutrophil complex formation was stimulated with ADP or PMA. We tested the effect of different sample preparation steps and cytometer settings on platelet-neutrophil complex detection and noticed false-positive counts with increasing acquisition speed. Platelet-neutrophil complex formation depends on platelet P-selectin expression, and antibody blocking of P-selectin consequently prevented ADP-induced platelet-neutrophil complex formation. These findings may help generating more comparable data among different research groups that examine platelet-neutrophil complexes as a marker for cardiovascular disease and novel therapeutic interventions.